Low-Dose Chemotherapy with Insulin (Insulin Potentiation Therapy) in Combination with Hormone Therapy for Treatment of Castration-Resistant Prostate Cancer. (8th May 2012) - Damyanov, Christo; Gerasimova, Desislava; Maslev, Ivan; Gavrilov, Veselin
Abstract : Purpose . To evaluate the results and quality of life of patients with resistant of castration-resistant tumors previously treated with Insulin-potentiation therapy (IPT) combined with hormone therapy. Materials and methods . Sixteen patients with metastasis prostate tumors after bilateral castration, androgenic blockade, and progression of the disease were observed during the study. The patients were divided into two groups: group A consisting of 8 patients treated with low-dose chemotherapy Epirubicin, Vinblastine, and Cyclophosphamide combined with LHRH agonist and group B consisting of another 8 patients treated with low-dose chemotherapy Docetaxel combined with LHRH agonist. Results . The overall (groups A and B) results concerning PSA after the sixth IPT show partial effect in 8 out of 16 (50%) patients, stabilization in 4 out of 16 (25%), and progression in 4 out of 16 (25%). The median survival for all treated patients is 11, 7 months (range 3–30 months). During the treatment no significant side effects were observed, and no lethal cases occurred. Conclusion . In spite of the small number of the treated patients with castration-resistant prostate tumors, the preliminary results are promising and this gives us hope and expectations for future serious multicenter research over the possibilities for routine implementation of IPTLD.